Body mass index, HbA1c and serum C‐reactive protein are predictors of secondary failure in infliximab continuance for Japanese psoriasis patients: A hospital‐based retrospective case‐control study. Issue 11 (6th August 2021) - Terui, Hitoshi; Asano, Masayuki; Shimada‐Omori, Ryoko; Tsuchiyama, Kenichiro; Takahashi, Toshiya; Nasu‐Tamabuchi, Mei; Hagiwara‐Takita, Akiko; Kusakari, Yoshiyuki; Ohtani, Tomoyuki; Aiba, Setsuya; Yamasaki, Kenshi
Abstract: Biologics has had a great impact on psoriasis treatment as well as the life of psoriasis patients. Infliximab (IFX), one of the biologics targeting tumor necrosis factor (TNF), is the first of the biologics introduced to Japanese psoriasis patients. Many patients had benefits of IFX from initial applications and sustained remission of skin lesions and arthritis. Some, however, fall into so‐called secondary failure, in which patients become less responsive to IFX when the treatment is repeated. The mechanism of secondary failure and the background of patients with secondary failure have not been completely elucidated. To address this issue, we retrospectively evaluated psoriasis patients treated with IFX in our department. In this retrospective, single‐center, case‐control study based on the clinical record, a total of 34 patients were enrolled. We excluded 7 patients who discontinued IFX because of adverse events of IFX. We divided other 27 patients into two groups; 16 patients who kept using IFX (Continuance group); and 11 patients who switched to other treatments (Discontinuance group). Among various clinical features, body mass index (BMI), HbA1c, and serum CRP level were significantly higher in the Discontinuance group than the Continuance group. The results indicated that these three clinical features of BMI, HbA1c and serum CRP level before treatment are the predictors of successful IFX treatment and suggest that improvement of metabolic conditions contributes to avoiding secondary failure and discontinuance of IFX.